Drivers of Crime and Violence in Papua New Guinea - Lakhani, Sadaf; Willman, Alys M. (World Bank, Washington, DC, 2014)
Reports in both the national and international media and anecdotal evidence indicate that the prevalence of crime and violence is high in PNG, and presents an important obstacle to long-term development. A growing body of literature and data on the issue identify a diverse range of forms of crime and violence; from violence in the household to violent conflict between clans, and various forms of interpersonal violence. This violence has been linked to various factors, ranging from historical and cultural factors, to, more recently, economic drivers. Conflict and violence have historically been an integral part of social life in PNG. This briefing note presents an analysis of the drivers of violence and crime in PNG. An extensive data and literature review was undertaken by a World Bank team, following a scoping mission to PNG in December 2011. A follow-up mission to Port Moresby in October 2012 which included individual consultations with stakeholders as well as an experts meeting on Conflict and Fragility helped test and refine the analysis. The brief begins with a description of the role of conflict in PNG society, and of traditional mechanisms for managing conflict. Next, it discusses key stresses that increase the risk of violence in PNG. The fourth section examines how these stresses affect the capacity of institutions in PNG to manage the conflicts that come with rapid social and economic changes. The brief concludes with a summary of gaps in the current understanding of the stresses and drivers of violence in PNG.